The Obstacles of Implementing Blended Learning Teaching from the Perspectives of Intellectual Disabilities Teachers in Jeddah - Al-Sulami, Seham Hamadi; Sahab, Lama AbdulHakeem (Journal of Educational and Psychological Sciences, 2023)
This study aimed at identifying the obstacles of applying blended education in the educational process according to viewpoint of teachers of students with intellectual disabilities in Jeddah, and to know the differences between these obstacles according to the variables of the study. This study used the descriptive survey method and applied a questionnaire, prepared by the researcher, to a sample of (148) teachers of students with intellectual disabilities in Jeddah origin (291). The results of the study revealed that the obstacles of applying the blended education in the educational process according to the viewpoint of teachers of students with intellectual disabilities in Jeddah were of large degree. It became clear that the dimension (technical and material obstacles) was in the first rank and with a very large degree, followed by the dimension (obstacles related to the curriculum and educational activities) which was of large degree and it was in second rank, the third rank was the dimension (general obstacles) which also was of large degree, and in the fourth rank was the dimension (obstacles related to teachers of students with intellectual disabilities) which also was of large degree, and in the last fifth rank was the dimension (obstacles related to students with intellectual disabilities), which also was of large degree. The results of the study also showed that there were no significant statistical differences at the level of (0.05) in the assessment of teachers of students with intellectual disabilities for the obstacles of applying the blended education due to the variables (educational qualification, years of experience, and the number of courses they obtained in the last 5 Years in the field of technology, and the nature of the program), while it became clear that there were only significant statistical differences between responses of the sample with regard to: (obstacles related to teachers of students with intellectual disabilities) due to the variable nature of the program toward the teachers working in intellectual education institutes, One of the most prominent recommendations training courses and workshops for teachers of intellectually disabled students.